হিন্দু জনগোষ্ঠীর একাত্তর - চৌধুরী, আফসান. (ঢাকা : ইউনিভার্সিটি প্রেস লিমিটেড, 2020)
On the history and struggle of Hindu community from Bangladesh, during 1971 Liberation war.
GenEd
ENH
Book Finder International
In Bengali.
Keywords: Bangladesh -- History -- Revolution, 1971.; বাংলাদেশ -- ইতিহাস -- মুক্তিযুদ্ধ, ১৯৭১.